Exact estima tes for the rate of convergence of the s-step method of steepest descent in eigenvalue problems - Bondarenko, L. N.; Zhuk, P. F. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We obtain exact (unimprovable) estimates for the rate of convergence of the s-step method of steepest descent for finding the least (greatest) eigenvalue of a linear bounded self-adjoint operator in a Hilbert space.